Cheap Sox Alumni Reunion Show in Goddard Chapel for Homecoming/Parents' Weekend. Photo 062 - Loeb, Brian (Tufts Archival Research Center, 2008)
Cheap Sox Alumni Reunion Show in Goddard Chapel for Homecoming/Parents' Weekend.